HAPPINESS AND THE RESTLESS HEART: AN AUGUSTINIAN CONFESSION. Issue 1 (19th February 2014) - Johnson, Luke Timothy
Abstract Saint Augustine opens his Confessions with the words "Great art thou, O Lord, and greatly to be praised; great is thy power, and of thy wisdom there is no number. . . . this tiny part of all that Thou hast created desires to praise Thee. Thou dost so excite him that to praise Thee is his joy. For Thou hast made us for Thyself and our hearts are restless until they rest in Thee." The author discovered these words, in the translation of Frank Sheed (New York: Sheed & Ward, 1943), at a young age, and the concluding line in particular, "For Thou hast made us for Thyself and our hearts are restless until they rest in Thee, " has occasioned continual return and reflection. In this article, the author investigates the meaning of this line in its context, following the phrase "to praise Thee is his joy." Adopting a generous construal of his own experience with the text, the author examines some of the ways in which a person who wishes to be a Christian thinks about the elusive yet all-important dimension of human existence called happiness or joy.